Cellular Oxidative Stress - Marino, Angela; Dossena, Silvia (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book collects 17 original research papers and 9 reviews that are part of the Special Issue "Cellular Oxidative Stress", published in the journal Antioxidants. Oxidative stress on a cellular level affects the function of tissues and organs and may eventually lead to disease. Therefore, a precise understanding of how oxidative stress develops and can be counteracted is of utmost importance. The scope of the book is to emphasize the latest findings on the cellular targets of oxidative stress and the potential beneficial effect of antioxidants on human health.